Quantifying biochemical quality parameters in carrots (Daucus carota L.) – FT-Raman spectroscopy as efficient tool for rapid metabolite profiling. (1st December 2016) - Krähmer, Andrea; Böttcher, Christoph; Rode, Andrea; Nothnagel, Thomas; Schulz, Hartwig
Highlights: FT-Raman spectroscopy was used for quantification of various metabolites in carrots. Sum of carotenoids, α -carotene and β -carotene can be predicted with R 2 > 0.96 each. Polyacetylenes and falcarindiol were predicted with R 2 = 0.91 and 0.90, respectively. Carbohydrates, fructose, glucose and sucrose were quantified with R 2 > 0.96. PCA of FT-Raman spectra revealed metabolic variety of different Daucus carota L. Abstract: Application of FT-Raman spectroscopy for simultaneous quantification of carotenoids, carbohydrates, polyacetylenes and phenylpropanoids with high bioactive potential was investigated in storage roots of Daucus carota . Within single FT-Raman experiment carbohydrates, carotenoids, and polyacetylenes could be reliably quantified with high coefficients of determination of R 2 > 0.91. The most abundant individual representatives of each compound class could be quantified with comparably high quality resulting in R 2 = 0.97 and 0.96 for α -carotene and β -carotene, in R 2 = 0.90 for falcarindiol (FaDOH), R 2 = 0.99, 0.98 and 0.96 for fructose, glucose and sucrose. In contrast, application of FT-Raman spectroscopy for quantification of two laserine-type phenylpropanoids was investigated but failed due to low concentration and Raman response. Furthermore, evaluation of metabolic profiles by principle component analysis (PCA) revealed metabolic variety of carrot root composition depending on root color and botanical relationship.